Pengaruh Kepercayaan, Kemudahan dan Kualitas Pelayanan terhadap Keputusan Pembelian di Tokopedia pada Mahasiswa Fakultas Psikologi UNPRI - Pardosi, Amanda Ulyana; Br Tariga, Risdayanti; Limbong, Chrislyn Becky Nancy; Faris, Salman (JEBIM Prima, 2025)
This study aims to analyze the effect of trust, convenience, and service quality on purchasing decisions in Tokopedia, especially among students of the Faculty of Psychology, University of Prima Indonesia. The background of this study is the rapid development of e-commerce in Indonesia, which requires an in-depth understanding of the factors that influence consumer behavior, especially the younger generation. The method used is a quantitative approach with a survey, involving 100 student respondents selected through purposive sampling technique. Data were collected using questionnaires and analyzed by multiple linear regression. The results showed that the variables ease and quality of Service have a positive and significant effect on purchasing decisions. Meanwhile, Trust did not show a partially significant effect. However, simultaneously, all three variables have a significant influence on the purchase decision. The contribution of the three variables to the purchase decision reached 82.92%, while 17.08% were influenced by other factors outside this study. These findings emphasize the importance of ease and quality of service in improving student purchasing decisions at Tokopedia.